Conservation of architectural heritage during the soviet period: between science and creation - Drūlytė-Butkevičienė, Jolita (Journal of Architecture and Urbanism, 2012)
The research focused on problems pertaining to restoration of missing parts of rebuilt and reconstructed buildings in Lithuania during the Soviet period. Solutions to such problems very much depended on the amount of available authentic data. The most accurate solution is to use scientific research information, which is based on architectural research or objective visual material. This type of restoration reveals the previous view of a fragment. As a result, application of this method allows restoration of the missing parts and helps rebuilding the destroyed composition. In the case of logical interpretations inspired by scientific research,scientific information is not sufficient for complete restoration of fragments; thus, the missing data is received by mathematical counting. This type of restoration makes it impossible to strongly state the degree, to which the restored information coincides with the previous view and whether it fulfils the rules of international conservation. In the case of a mixture of scientific research and creative interpretation, remains of authentic fragments are insufficient to restore an object. As a consequence, the missing fragment parts are created seeking for the composite unity. Similarly, when creative interpretation is used, authentic information only shows that there has been a specific detail, but there are no data about its exterior, therefore, the lost detail has to be created. The last two ways contradict to the rules of international conservation. It is important to emphasize that observers often concentrate their criticism around the lack of information objectivity. In buildings, it is not possible to distinguish between repetitions of authentic forms and the 20th century interpretations. Thereby, one of the most important values, the cognitive one, loses its meaning. Article in Lithuanian. Sovietinių metų paveldotvarkos darbai: tarp mokslo ir kūrybos Santrauka. Atlikus tyrimą nustatyta, kad sovietiniais metais restauruojant ir rekonstruojant pastatus Lietuvoje trūkstamų dalių atkūrimo problemos priklausomai nuo autentiškos medžiagos kiekio buvo sprendžiamos keliais būdais. Mokslinių tyrimų informacija – pats tiksliausias architektūros tyrimais ar objektyvia vaizdine medžiaga pagrįstas atkūrimas atskleidžiant tikslų buvusį fragmento vaizdą. Taip atkurtos trūkstamos dalys padeda sugrąžinti sunaikintą kompoziciją. Mokslinių tyrimų inspiruotos loginės interpretacijos atveju fragmentui visiškai atkurti mokslinės informacijos neužtenka, trūkstami duomenys gaunami atliekant matematinius skaičiavimus. Šiuo atveju negalima tiksliai nustatyti, kiek atkurtoji informacija atitinka buvusį vaizdą ir kiek toks veiksmas atliepia tarptautines paveldotvarkos nuostatas. Kiti du naudoti būdai akivaizdžiai prieštarauja tarptautinės paveldotvarkos nuostatoms. Mokslinių tyrimų ir kūrybinio interpretavimo derinio atveju išlikusių autentiškų fragmentų neužtenka objektui visiškai atkurti, todėl, siekiant kompozicinės vienovės, trūkstamos fragmentų dalys sukuriamos. Kūrybinės interpretacijos atveju autentiška informacija tik parodo, kad konkrečios detalės būta, tačiau duomenų apie jos išvaizdą nėra, – tada toji detalė sukuriama. Reikia akcentuoti, kad pastatuose, kuriems buvo atlikti paveldotvarkos darbai, vizualiai neįmanoma atskirti autentiškų formų pakartojimų ir XX a. pab. interpretacijų, dėl to savo prasmę praranda viena iš svarbiausių – pažintinė – vertė. Reikšminiai žodžiai: architektūros restauravimas, rekonstravimas, moksliniai tyrimai, loginė interpretacija, kūrybinė interpretacija.